Bridging Technology and Cognition: A Systematic Review of Animation-Based Mathematics Learning Trends - Sulastri, Desi; Nurhikmayati, Iik; Aligaya, Dexter C (Jurnal Pendidikan MIPA, 2025)
This systematic literature review analyzes 27 empirical studies published between 2020 and 2024 on the use of animation in mathematics learning by applying the PRISMA protocol within a Critical Interpretive Synthesis (CIS) framework, complemented by keyword co-occurrence analysis, heatmap visualization, thematic analysis of 27 abstracts, and a relational mapping Sankey diagram. Descriptively, publication trends show a fluctuating pattern with the most significant surge occurring in 2023 (9 publications), predominantly from Indonesia (≈40%), followed by African and European countries, and by experimental (33.3%) and R&D (25.9%) designs. The most frequently investigated mathematical competency is conceptual understanding (37.0%), whereas higher-order skills such as HOTS, reasoning, and mathematical connections remain marginal. The distribution of animation platforms is dispersed, with no single dominant tool, including Powtoon, GeoGebra, and animated videos (each at 11.1%). Keyword co-occurrence analysis yields six clusters, centered on the GeoGebra–geometry cluster, with the mathematical connection node positioned the most independently, indicating weak theoretical integration in that area. The heatmap and Sankey diagram reveal unbalanced cross-dimensional relationships, highlighting that links among methodology, mathematical competencies, and platforms are more strongly shaped by institutional preferences and technological readiness than by cognitive demands. The thematic analysis identifies five major themes: (1) the effectiveness of animation in supporting conceptual representation, (2) cognitive mechanisms such as segmentation and cognitive load reduction, (3) enhancement of motivation and engagement, (4) technology integration and teacher readiness, and (5) implementation constraints, including reliance on demonstration and lack of theoretical integration. The methodological quality assessment indicates small sample sizes, short intervention durations, inconsistent instruments, and potential publication bias. Future research should integrate stronger theoretical frameworks, expand its focus on higher-order competencies, and conduct longitudinal and comparative studies across platforms to strengthen the empirical basis for the use of animation in mathematics education.    Keywords: animation, mathematics education, technology, systematic literature review.